Declarative and procedural tactical knowledge in youth soccer players: an exploratory study in Chile - Ricardo Souza de Carvalho; Eugenio Merellano Navarro; Manuel González-Farías; Jorge Mendez-Cornejo; Alejandro Almonacid-Fierro (Pedagogy of Physical Culture and Sports, 2025)
Background and Study Aim. Tactical knowledge, both declarative and procedural, is an essential component of cognitive development in youth soccer. The aim of this study is to describe and analyze the declarative and procedural tactical knowledge of youth football players from a professional club in southern Chile.